Effects of Soil Conservation Practice and Crop Rotation on Selected Soil Physicochemical Properties: The Case of Dembecha District, Northwestern Ethiopia - Melkamu Degu; Asmare Melese; Wondwosen Tena (Applied and Environmental Soil Science)
Crop rotation systems especially dominated by cereals (maize and wheat) are intimately linked to soil properties. The objective of the study was to investigate the effect of crop rotations and conservation practice on selected soil physicochemical properties in northwestern part of Ethiopia. Soil samples (0–20 cm depth) were collected from seven crop rotations with conservation practice and adjacent fields without any conservation measure in three replications. A total of forty-two composite samples were used for analysis by using SAS software. The land rotated with maize-wheat-faba bean exhibited significantly higher mean bulk density (1.06 g/cm3) than the land rotated with other crops (i.e., ranging from 1.02 to 1.04 g/cm3). Mean values of pH (5.34, 4.98, and 5.4), Ex. acidity (2.03, 2.53, and 2.16 cmolc/kg), soil OM (4.53%, 5.12%, and 5.02%), CEC (45.17, 48.03, and 49.47 cmolc/kg), TN (0.23, 0.25, and 0.27%), Av.P (10.21, 7.23, and 7.95 ppm), and C : N ratio (11.18, 11.95, and 10.8) were recorded under rotations with continuous maize, maize-pepper-pepper, and maize-faba bean-pepper, respectively. Mean values of pH (5.34 and 4.97), Av.P (9.51 and 6.53 ppm), CEC (48.3 and 46.87 cmolc/kg), and Ex. acidity (2.5 and 2.85 cmolc/kg) were also recorded under conserved and unconserved farmlands, respectively. Considering the interaction effect of crop rotations by conservation practice, all studied parameters, except bulk density, CEC, and C : N ratio, were significantly (p<0.05) affected. The findings indicate that although continuous maize showed good content of available P and low exchangeable acidity, it will deplete particular nutrients; therefore, maize-pepper-pepper, maize-wheat-faba bean, and maize-faba bean-pepper recorded a slight trend of good values in studied soil physicochemical properties compared to other rotations. A critical study on such type of issue should be carried out over a longer period of time in order to announce detailed understanding about response of soil property to crop rotations to the community.